Nate the Great and the Missing Birthday Snake - Sharmat, Marjorie Weinman; Wheeler, Jody (New York : Delacorte Books for Young Readers, 2017)
Join the worlds greatest detective, Nate the Great, as he solves the mystery of what happened to his friends pet snake. Rosamond is having a birthday party for her cousin Lizzy! Nate the Great and his dog, Sludge, are invited. So are Lizzys four pet snakes. Nate believes that a good detective knows his limits. Nate does not want to go to a birthday party filled with dangerous, slimy guests. But when one of these "guests" goes missing, Nate and Sludge must face their fears to save the day!
510L
Decoding demand: 69 (high)
Semantic demand: 83 (very high)
Syntactic demand: 57 (medium)
Structure demand: 82 (very high)
Accelerated Reader AR
Keywords: Nate the Great (Fictitious character) -- Juvenile fiction; Birthday parties -- Juvenile fiction; Snakes -- Juvenile fiction; Lost animals -- Juvenile fiction; Early readers; Chapter books